DISCOVERING TYROSINASE INHIBITORS FROM MORUS SP. PLANTS: AN IN SILICO STUDY - FALYA, YUNIARTI; AMELIA, RENNY; RIZIKIYAN, YAYAN; SULASTRI, LELA; HIDAYATI, NUR RAHMI (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to examine Morus sp. compounds bonding mode with critical amino acid residues in the binding pocket of the enzyme TRP1 in In silico so that it can be used as a support in the design of skin-lightening cosmetics based on Morus sp. Methods: Docking is done using autodock tools software, chem office 2019, ChemDraw professional 12, autodock 4.2, discovery studio 2016. Results: Isorhamnetin has two hydrogen bonds to amino acids Met215 and Asn205. Other compounds found in Morus sp., which have hydrogen bonds with Asn205, are dihydromorin, kaempferol, quercitrin, rutin, and morusin. Conclusion: Isorhamnetin has the best potential among other compounds as a tyrosinase inhibitor by hydrogen binding to the amino acid Met215, and Asn205 has a free energy of-6.16 kcal/mol.